البلاغة النبوية في منظور الرافعي: قراءة في المنهج Prophetic Eloquence According to al-Rafi'i: An Analysis of His Methodology - (Benaissa Bettahar), بن عيسى بطاهر (At-Tajdid - Intellectual Refereed Journal, 2014)
لقد كان مصطفى صادق الرَّافعي أحد أبرز الكتاب الذين عُنُوا بالبحث في البلاغة النبوية تنظيرًا وتطبيقًا، حيث سعى للكشف عن الخصائص الأسلوبية العامّة، والسمات التعبيرية التي تميّز بها الحديث الشريف عن سائر كلام العرب، كما حاول من خلال تحليلاته لبعض النصوص الكشف عن الأبعاد الدلالية والتجليات الجمالية التي تميّز بها الأسلوب النّبوي. وهذه الدراسة مقاربة نقدية لمنهج الرَّافعي في دراسته بلاغةَ الحديث النَّبوي الشَّريف، وذلك خلال استجلاء آرائه النظرية وتحليلاته التطبيقية، وتقويم منهجه من حيث الأصالة والتقليد، مع بيان أسباب اهتمامه بالحديث النّبوي الشريف ومسوّغاته في الدفاع عنه. الكلمات الأساسية: البلاغة النبوية، الخطاب النبوي، الحديث النّبوي، الخصائص الأسلوبية، الأبعاد الدلالية، التجليات الجمالية، كلام العرب، الرافعي. _______________________ Mustapha ØÉdiq al-RÉfiÑÊ was one of the most prominent writers who carefully studied the Prophet’s eloquence both theoretically and practically. He applied himself to unveiling the general stylistic features and modes of expression characterizing the Prophetic discourse and distinguishing it from the discourses of the Arabs. He also tried to unfold the semantic aspects and aesthetic manifestations of the Prophet’s style based on the analysis of certain texts. The present study consists of a critical approach to al-RÉfiÑÊ’s work in an attempt bring into light his theoretical views and applied analyses and evaluate his methodology in terms of originality and dependence. The study also highlights the reasons behind his interest in the Prophetic Traditions and his motives for defending them. Key Terms: Prophetic eloquence, Prophetic Traditions, Prophetic discourse, stylistic features, semantic aspects, aesthetic manifestations, Arabic discourses, al-RÉfiÑÊ.